Pendulous Urethral Stricture: Peculiarities and Relevance of Longitudinal Penile Fascio-Cutaneous Flap Reconstructionin Poor Resource Community - Salako, Abdulkadir Ayo; Olajide, Abimbola Olaniyi; Aremu, Ademola Adegoke; Afolayan, Michael O; Adejare, Ifeoluwa E; Oseni, Oyediran Ganiyu (Urology Journal, 2014)
Abstract PURPOSE: To describe peculiarities of pendulous urethral stricture in South Western Nigeria and how prevalent social and environmental factors have made longitudinal distal penile island flap the preferred option for reconstruction of pendulous urethral stricture in such a poor resource community. Materials and Methods: All patients presenting with stricture located in the pendulous urethra in 3 hospitals in south western Nigeria, over a 5 year period were interviewed and had urethral reconstruction using longitudinal distal penile fascio-cutaneous island flap under spinal anesthesia. Results: Thirty four cases were treated by this method during this period. Complications were found in 4 patients (11.8%) which include urethrocutaneous fistula, penile skin necrosis and wound infection. All cases had satisfactory overall outcome. Conclusion: Longitudinal penile fascio-cutaneous flap remains a viable option for a single stage repair of urethral stricture especially in poor resource communities.